(Manihot utilissima Pohl.)(The Effects of Sucrose and Citric Acid Concentration on the Co-crystallization of Fermented Cassava (Manihot utilissina Pohl) Extract) - Indra Neffi Ridwan; Titin Sriyogasari; Hendra Wijaya; Ela Turmala Sutrisno (Warta Industri Hasil Pertanian, 2004)
The purpose of this research is to study the effect of interaction between sucrose and citric acid concentration on the quality of co-crystallization of fermented cassava (manihot utillisima pohl). Extract. The benefit of this research is to diversify cassava fermented product in order to type of food product that is more pratical in its consumption. s a result this product will create an increasing economic value of cassava. The experiment was carried out using the randomized block desing withpattern factorial and 3 times replicating. The frist factor is sucrose concentration (40%; 50%; and 60%) and the second factor is citric acid concentration (1% ; 1.5%; and 2%). Parameter analyzed during the experiment were moinsture content, total sugar, solubility, and organoleptic test using prefence test type with 15 panelist which cover color, taste, flavor, and apperance. Basedc on the result of organoleptic test of microcrystal fermented cassava extract that perferred by panelist were it was produced with 40% of surcose and 1.5% of citric acid concentraction.  This fermented cassava extract produced by this methods contain moinsture content 2.14% and total sugar 56.05%, and has solubility 26.84%.